Wuchereria bancrofti Lymphatic Filariasis, Barrancabermeja, Colombia, 2023 (2024)
We describe a recent case of lymphatic filariasis in Colombia caused by Wuchereria bancrofti nematodes. Our study combines clinical-epidemiologic findings with phylogenetic data. Resurgence of lymphatic filariasis may be linked to increasing urbanization trends and migration from previously endemic regions. Fieldwork can be a beneficial tool for screening and containing transmission.